Longterm-habituation of the startle response in mice is stimulus modality, but not context specific - Pilz, Peter K.; Arnold, Stephan W.; Rischawy, Anja T.; Plappert, Claudia F. (Frontiers in Integrative Neuroscience, 2014)
In mice, the specificity of longterm-habituation (LTH) of startle was tested in two experiments. In two strains of mice (C57Bl/6 and C3H) there was pronounced LTH over 10 days of acoustic stimulation in two different contexts of startle measurement. (We found LTH to be greater after stimulation with 14 kHz sine stimuli compared to noise or tactile stimuli.) A change of context showed LTH to be independent of context, i.e. startle LTH in mice is a non-associative learning process. In the second experiment, 9 days of acoustic or tactile stimulation were given to C57B/6 mice. Both stimulus modalities produced LTH. When on the 10th day stimuli of the other modality were given, in both cases the long term habituated group showed no lower startle amplitude than a non-stimulated control group. This indicates LTH is stimulus-modality specific. Altogether, our results show that in mice—very similar to rats—LTH of startle is stimulus modality, but not context specific. In addition we found two indications that the LTH action site is on the sensory branch of the startle circuit.